2013
DOI: 10.1007/jhep07(2013)146
|View full text |Cite
|
Sign up to set email alerts
|

Minimal lepton flavour structures lead to non-maximal 2-3 mixing

Abstract: Present data prefer a large but non-maximal 2 − 3 mixing in the lepton sector. We argue that this value, in connection with sin θ 13 0.15, is the generic outcome of minimal flavour structures. We present a few different incarnations of this statement, in terms of lepton mass matrices depending on a small number of parameters, that can be justified by discrete flavour symmetries. We also propose a general procedure to study the correlation between θ 23 , the absolute scale and ordering of the neutrino masses, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…For instance, it has been shown that the two-zero textures in class 1 4 0 2 can be obtained from continuous or discrete flavour symmetries (see e.g. [4,6,28]), while the particular texture T 4, 6 25 of class 2 1 1 2 0 2 can be constructed through a flavour symmetry based on the order-twelve quaternion group Q 6 [26]. Similarly, the hybrid textures belonging to class 2 1 1 3 0 1 can be realised in a type-II seesaw framework by implementing certain discrete symmetries [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been shown that the two-zero textures in class 1 4 0 2 can be obtained from continuous or discrete flavour symmetries (see e.g. [4,6,28]), while the particular texture T 4, 6 25 of class 2 1 1 2 0 2 can be constructed through a flavour symmetry based on the order-twelve quaternion group Q 6 [26]. Similarly, the hybrid textures belonging to class 2 1 1 3 0 1 can be realised in a type-II seesaw framework by implementing certain discrete symmetries [11].…”
Section: Discussionmentioning
confidence: 99%
“…Particular cases of textures belonging to the class 2 1 1 2 0 2 have been previously considered in the literature. For example, the texture C 25 was analysed in [26], while the textures A 1,46 and A 2,46 with an additional constraint were found to be compatible with data at 3σ CL in [27]. We analysed all the textures of table 5 in order to search for extra correlations among the matrix elements of m ν .…”
Section: Textures With Four and Five Parametersmentioning
confidence: 99%